A Conceptual Model of Knowledge Management Practices and Internationalization of SMEs - Houssaini, Mohammed Sqalli (European Scientific Journal, ESJ, 2019)
This work aim is to study the relationship between the internationalization of SMEs and Knowledge Management practices. In order to better assimilate the behaviour of these companies, we will focus on their main features as well as the different forms of possible entries to foreign markets. Afterwards, interest will be focused on the role of knowledge in the internationalization process. Through the literature review, it turns out that researchers mainly focus on the perception, the implementation and the transfer of knowledge practices, while neglecting other aspects like identifying, sharing and applying knowledge. For this purpose, we will attempt to conceptualize relations that require more attention in future research. The proposed model can form a basis for future researches in International Business and Knowledge literature.